2017
DOI: 10.1038/ncomms16063
|View full text |Cite
|
Sign up to set email alerts
|

SRSF1-dependent nuclear export inhibition of C9ORF72 repeat transcripts prevents neurodegeneration and associated motor deficits

Abstract: Hexanucleotide repeat expansions in the C9ORF72 gene are the commonest known genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia. Expression of repeat transcripts and dipeptide repeat proteins trigger multiple mechanisms of neurotoxicity. How repeat transcripts get exported from the nucleus is unknown. Here, we show that depletion of the nuclear export adaptor SRSF1 prevents neurodegeneration and locomotor deficits in a Drosophila model of C9ORF72-related disease. This intervention suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
157
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(169 citation statements)
references
References 70 publications
(132 reference statements)
9
157
1
Order By: Relevance
“…Since SRSF1 is involved in both splicing and nuclear export functions, the reporter constructs were also designed without splicing consensus sites or intronic sequences to allow for specific investigation of the SRSF1-dependent nuclear export potential of G4C2 and C4G2 repeat sequences in absence of functional coupling to splicing. Interestingly, the expression of uninterrupted G4C2x38 or C4G2x39 repeat transcripts which lead to the production of DPRs, but not of G4C2/C4G2x15 repeat transcripts which do not, is much more potent at inhibiting neuronal cell proliferation (by approximately 50%, 48 hours post transfection) [45] than transfection (not shown) or stable integration [47] of interrupted transcripts harboring 102 repeats of the G4C2 sequence -in direct correlation with the expression levels of DPRs. Depletion of ~70% of the SRSF1 protein in neuronal N2A cells transfected with the DPR-reporter constructs further led to an efficient inhibition of the nuclear export and subsequent RAN translation of sense/ antisense repeat transcripts which correlated with a suppression of the C9ORF72 repeat-mediated cytotoxicity in cell proliferation assays.…”
Section: Srsf1-dependent Nuclear Export Of Sense and Antisense C9orf7mentioning
confidence: 97%
See 4 more Smart Citations
“…Since SRSF1 is involved in both splicing and nuclear export functions, the reporter constructs were also designed without splicing consensus sites or intronic sequences to allow for specific investigation of the SRSF1-dependent nuclear export potential of G4C2 and C4G2 repeat sequences in absence of functional coupling to splicing. Interestingly, the expression of uninterrupted G4C2x38 or C4G2x39 repeat transcripts which lead to the production of DPRs, but not of G4C2/C4G2x15 repeat transcripts which do not, is much more potent at inhibiting neuronal cell proliferation (by approximately 50%, 48 hours post transfection) [45] than transfection (not shown) or stable integration [47] of interrupted transcripts harboring 102 repeats of the G4C2 sequence -in direct correlation with the expression levels of DPRs. Depletion of ~70% of the SRSF1 protein in neuronal N2A cells transfected with the DPR-reporter constructs further led to an efficient inhibition of the nuclear export and subsequent RAN translation of sense/ antisense repeat transcripts which correlated with a suppression of the C9ORF72 repeat-mediated cytotoxicity in cell proliferation assays.…”
Section: Srsf1-dependent Nuclear Export Of Sense and Antisense C9orf7mentioning
confidence: 97%
“…In our recent study, we also showed that SRSF1-m4 directly interact with G4C2x5 and C4G2x5 synthetic RNA probes and is sequestered in a length dependent manner onto G4C2-sense and C4G2-antisense repeat transcripts in neuronal N2A cells. Expression of the SRSF1-m4 mutant protein also resulted in nuclear retention of the repeat transcripts and in reduced DPR production [45] , has not yet been investigated. It might involve recruitment of the TREX complex by uncharacterised nuclear adaptor(s) (NEA) and/or coupling to other SR-rich NEAs such as SRSF3 or SRSF7 (SR) during splicing.…”
Section: Srsf1-dependent Nuclear Export Of Sense and Antisense C9orf7mentioning
confidence: 99%
See 3 more Smart Citations